CFD-based simulation of outdoor natural ventilation for multiple buildings in Singapore Industrial Park - Mohamad Affindi Bin Mohd Ali (Nanyang Technological University, 2025)
The main objective of this project report is to investigate airflow patterns within multiple buildings in Singapore’s industrial park. This is achieved by utilising the technology of Computational Fluid Dynamics (CFD) to simulate study models for improving natural outdoor ventilation. In this research, four different simulation models were used in the CFD analysis. Wind velocity, pressure and temperature distribution around the four models are analysed by simulating contours and velocity vectors at different planes and locations. After analysing the results and output obtained, it is concluded that wider gaps in between buildings, optimal wind-facing orientation and circular shaped buildings are better for ventilation as well as maintaining a lower temperature.